5-aminolevulinic acid-based photodynamic therapy in combination with antifungal agents for adult kerion and facial ulcer caused by Trichophyton rubrum - Juan Ji; Chu-ting Liang; Jiao-jiao Zhong; Xue Kong; Hao-xiang Xu; Chang-chun Xu; Mei-hua Fu (Photodiagnosis and Photodynamic Therapy)
Dermatophytosis is the most common fungal infectious disease in the world, which is commonly caused by Trichophyton rubrum in China. The traditional therapies for treating dermatophytosis include topical and oral antifungal agents like terbinafine, griseofulvin, and azole antifungal drugs. However, 5-aminolevulinic acid-based photodynamic therapy (ALA-PDT) as a new alternative therapy avoids the side effects and drug resistance of traditional antifungal agents. We report two cases diagnosed as kerion and tinea faciei secondary to ulcers with CARD 9 deficiency, both of whom were infected by T.rubrum. They were both successfully treated by ALA-PDT combined with antifungal drugs, providing a feasible strategy for therapeutic choice for adult kerion and ulcer treatment.